PB ISOTOPIC COMPOSITION OF GRANITOIDS FROM THE ALTAY OROGEN (CHINA): EVIDENCE FOR MANTLE-DERIVED ORIGIN AND CONTINENTAL GROWTH - Tong Y.; Wang T.; Hong D.; Han B. (My University, 2006)
In the study of the sources of the Altay granitoids, Pb isotopic composition of feldspar from various typical syn-orogenic and post-orogenic and mafic intrusions from the Altay are analyzed. The results show that the granites have 206Pb/204Pb values between 17.997 and 18.921 (averaging 18.269), 207Pb/204Pb values between 15.460 and 15.599 (averaging 15.528), 206Pb/204Pb values between 37.661 and 38.262 (averaging 37.954) and μ values from 9.19 to 9.71 (mainly from 9.30 to 9.60). In various lead diagrams, these samples are mostly located in the fields of oceanic island volcanic rocks and are volcanic rocks, and all are far away from the upper crust, lower crust and pelagic sediments area. These suggest that the sources of the granitoids are similar to those of oceanic island volcanic rocks. In addition, the Pb isotopic composition of mafic intrusions being coeval with the granitoids has similar features. The result suggests that juvenile mantle-derived compositions have contributed to the formation of granites. This is consistent with previous studies related to Sr and Nd isotopes. Clearly, these granitoids differ from those from other orogens, such as the South China orogen and Himalayan orogen. This study provides new evidence for continental crustal growth in the central Asian orogenic belt during the Phanerozoic.
Keywords: CENTRAL ASIA; CONTINENTAL GROWTH; GRANITOIDS; MANTLE-DERIVED SOURCE; PB ISOTOPE